43 - PARTICIPATION OF NURSING IN REDUCING THE OCCURRENCE OF HOUSEHOLD ACCIDENTS FOR CHILDREN: BIBLIOGRAPHIC STUDY (Fiep Bulletin - online, 2011)
Introduction: Currently, despite advances in health, child accident still a serious problem worldwide, and the home environment is the place where such events occur frequently. This reality is due, in part, the association between curiosity, low psychomotor development inherent in the age and the long period that the children remain at home. Objectives: To characterize children who are victims of domestic accidents, according to the literature regarding gender and age, to identify the predisposing conditions for the occurrence of events, the types of most frequent accidents and recommending action by professionals to minimize the issue. Material and Methods: This is a bibliographical research in the portal of the Virtual Health Library (BIREME), of which 25 were selected publications. Results: Most victims were male, belonging to the age of one to four years, and many events occurred in the presence of adults, highlighting the failure to promote a safe environment for children. The types of accidents questions were, respectively, Burns 17 (27.9%), falls 16 (26.2%), poisoning and 13 (21.3%), however, falls were listed by the articles in general and the main types of occurrences. Thus, to minimize the problem, the nurse must realize the seriousness of this, and expand educational programs for children and adults for the prevention of childhood accidents
Keywords: Domestic Accidents; Child; Risk Factors